The person undergoing total hip arthroplasty due to coxarthrosis - Pedro Dias; Rogério Ferrinho Ferreira; Patrícia Messias (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Biological changes duo to aging can cause joint problems and coxarthrosis is one of the most common. Due to the consequences and the way it affects people's quality of life, total hip arthroplasty appears as one of the solutions. Thus, the rehabilitation nurse stands out as the professional capable of enhancing functionality and maximizing the person's independence. Objective: Identify the benefits of the rehabilitation nurse's intervention, in the pre and postoperative period of a person undergoing total hip arthroplasty due to coxarthrosis. Methodology: Unique descriptive case study, based on the CARE guidelines (CAse REport). A specific rehabilitation program was implemented and targeted at the person under study, based on the diagnoses identified and giving particular interest to Functional Motor Reeducation. Results: There was an increase in muscle strength and range of motion in the surgically operated limb, improvements in body balance and independence in performing activities of daily living and a decrease in the risk of falling and pain intensity. Conclusion: Functional capacity improved after surgical intervention and a rehabilitation nursing program.